CLINICAL CHARACTERISTICS AND SURGICAL OUTCOMES OF PELVIC ORGAN PROLAPSE TREATMENT AT THAI BINH UNIVERSITY HOSPITAL (2021–2025) (Vietnam Journal of Community Medicine, 2026)
Background: Pelvic organ prolapse is a common pelvic floor disorder among middle-aged and older women and may adversely affect daily activities, physical function, and quality of life. Local evidence on the clinical characteristics and short-term surgical outcomes of pelvic organ prolapse remains important for improving perioperative management and surgical care.Objective: This study aimed to describe the clinical characteristics and short-term surgical outcomes of patients undergoing surgical treatment for pelvic organ prolapse at Thai Binh University Hospital during 2021–2025.Methods: A descriptive observational study was conducted among 82 patients diagnosed with pelvic organ prolapse and treated surgically at Thai Binh University Hospital between January 2021 and December 2025. Data were collected from medical records and clinical follow-up during hospitalization. The main variables included demographic characteristics, menopausal status, parity, clinical manifestations, prolapse severity, surgical technique, operative duration, and intraoperative and postoperative complications. Descriptive statistics were used to summarize the findings.Results: Most patients were postmenopausal, and a high proportion had a history of three or more childbirths. Advanced pelvic organ prolapse accounted for the majority of cases, with grade III prolapse observed in approximately four-fifths of the study population. Lower urinary tract symptoms were recorded in about one-third of patients, while perineal trauma and cervical lesions were commonly documented. The most frequent anatomical pattern was uterine prolapse combined with posterior vaginal wall prolapse, followed by uterine prolapse with cystocele and anterior vaginal wall prolapse. Crossen surgery was the most commonly performed procedure, accounting for 81.7% of cases. The mean operative duration was 62.65 ± 6.18 minutes. No intraoperative complications were recorded. Postoperative complications were uncommon, with urinary retention, fever/infection, postoperative bleeding, and hematoma being the main events observed before discharge.Conclusion: Patients undergoing surgery for pelvic organ prolapse at Thai Binh University Hospital were predominantly postmenopausal and commonly presented with advanced-stage prolapse. Crossen surgery was the principal surgical approach. The short-term perioperative outcomes were generally favorable, with no recorded intraoperative complications and a low frequency of postoperative complications. Further studies with longer follow-up and standardized patient-reported outcome measures are needed to evaluate recurrence, functional recovery, and long-term treatment effectiveness.
Keywords: pelvic organ prolapse; uterine prolapse; Crossen surgery; surgical outcomes; postoperative complications; Vietnam.